Traumatic Posterior Tibial Pseudoaneursym: A rare late complication repaired conventionally - Farzad Amiri; Zachary Sanford; Constantinous Constantinou (Marshall Journal of Medicine, 2016)
Posterior tibial artery pseudoaneurysms are extremely rare. They commonly present as a late complication of trauma or iatrogenic injury. Diagnosis can be elusive. Treatment has been described in the context of open primary repair, endovascular stenting, and coil embolization. There has been increasing interest in the use of endovascular treatment options for this type of injury. If left untreated, pseudoaneurysms can rupture, partially thrombose, expand and cause adjacent local compression and compartment syndrome. The following case presented is of a young gentleman with a posterior tibial pseudoaneurysm incidentally discovered after stepping on glass and the management of his posterior tibial pseudoaneurysm.